Pemberdayaan Pendidikan Literasi Anak Sekolah Dasar melalui Pojok Membaca di Desa Tamansuruh - Jefry Aulia Martha; Galang Bintang Pramudya; Dewi Apriliyani; Dewi Oktaviani Tulung; Mohammad Hilfi Azra Dzikrulloh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
Pandemic COVID-19 has changed the world of education. All schools finally implemented learning from home with the model of students learning from home. As a result, a lot of things have changed, from the mindset to the way of learning. The problem was the background, the KKN team went home to create a reading corner activity. Reading is an important activity in everyday life, because it is not only to obtain information, but can also be a tool to expand one's knowledge and style of language so that with this activity participants are expected to improve their reading literacy skills. The activity was carried out on June 14, 2021 at SDN 3 Tamansuruh, while the methods used were in the form of preparation, implementation, and evaluation stages. Activities carried out include making reading corner shelves, collecting books, reading mentoring, and competitions. With this activity, it is hoped that in the future the children will be more happy to visit and be interested in reading books.